Triassic clam shrimps (“Conchostraca”; Branchiopoda: Diplostraca) from Mallorca: Taxonomic description and interregional comparisons - Scholze, Frank; Matamales-Andreu, Rafel (Zootaxa, 2021)
We describe four upper Lower Triassic to lower Middle Triassic clam shrimp-bearing intervals from Mallorca, which include the clam shrimp species Hornestheria sp. aff. Hornestheria sollingensis and several other forms of carapace valve morphology: Hornestheria? Morphotype 1, Hornestheria? Morphotype 2, and other undetermined carapace valves. All of this material was obtained from red-bed units cropping out in the Serra de Tramuntana mountains of Mallorca (western Mediterranean). Except for a few morphologically similar carapace valves of Middle Triassic age from China, Hornestheria is known only from the type locality of its type species, Hornestheria sollingensis Kozur et Lepper, in the Solling Formation (Middle Buntsandstein Subgroup) in the German part of the Central European Basin. According to its original definition, the larval carapace valve of Hornestheria Kozur et Lepper is characterized by a radial sculpture, but this characteristic apparently is only variably developed. Due to both a limited number of previously known occurrences of Hornestheria and its poorly known carapace valve morphology, open nomenclature is applied to the taxonomy herein. The studied specimens were freshly collected from outcrop sections composed of greyish-green to greyish-red laminated claystones and siltstones that accumulated in a fluvial facies. The clam shrimp specimens are accompanied by remains of insects and fishes, invertebrate and tetrapod ichnofossils, and micro-/macroplant remains, all of which either have been described by previous workers or are currently part of a separate study.